Labour migration of parents and threats to children and youth - Artur Kraus; Natalia Wojtas (Journal of Risk and Financial Management, 2021)
Labour migration is a global trend that shapes communities and economies around the world. Growing economic migration carries a specific threat to children and youth. Long-term consequences threaten life outcomes such as educational achievement, career development, mental and physical health. The study examined the problems of children from migrating families in educational institutions. It was also important to determine what assistance is provided to children from migrant families and what institutions support such families. The respondents were class tutors/educators who were teachers of educational institutions: 2317 respondents took part in the study, including 2044 women and 273 men. Significant differentiation of the respondents according to gender is mainly due to the feminization of the teaching profession in Poland. The results of the survey were analyzed with the chi-square test of independence. As a result of the research, threats to children and adolescents resulting from the economic migration of parents were diagnosed. In secondary schools, a decrease in attendance is observed (unexcused absences, truancy, being late). In lower secondary schools there are problems with school results and a decrease in motivation to learn. Educational institutions find it difficult to stay in contact with parents. In the youngest children (kindergartens, primary schools), emotional instability is observed due to the absence of parents in everyday contact. Educational institutions respond to diagnosed problems by providing support to students. In primary schools, students are provided with help in learning and students' free time is organized. There are also activities aimed at providing additional nutrition. In lower secondary schools, as in secondary schools, support focuses more on motivational interviewing, mediation in conflict situations and psychological assistance. In order to solve problems and help students, educational institutions cooperate with the Psychological and Pedagogical Counselling Centre, the Social Welfare Centre and the Probation Officer.
Keywords: 330; adolescent; child; health; income distribution/inequality; left-behind children; mental health; migrant worker; parent-child separation; psychosocial support; school